2008
DOI: 10.1089/hgt.2008.060
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of High and Low Voltage Pulse Combinations for Gene Electrotransfer in Muscle, Liver, Tumor and Skin

Abstract: Gene electrotransfer is gaining momentum as an efficient methodology for nonviral gene transfer. In skeletal muscle, data suggest that electric pulses play two roles: structurally permeabilizing the muscle fibers and electrophoretically supporting the migration of DNA toward or across the permeabilized membrane. To investigate this further, combinations of permeabilizing short high-voltage pulses (HV; hundreds of V/cm) and mainly electrophoretic long low-voltage pulses (LV; tens of V/cm) were investigated in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 35 publications
6
82
0
Order By: Relevance
“…This high field is lower than that used for skin (200 V cm À1 ), but much higher than that used in the combination protocol for muscle (80-100 V cm À1 ). 18 The differences in transfection efficiency between different tissues, as well as different tumor histological types, can be explained by the unique characteristics of each tissue, 5,26 namely, the delivery and distribution of macromolecules, including plasmid DNA, is affected by the amount of DNases, necrosis and macrophage infiltration as well as increased interstitial fluid pressure and the amount of extracellular matrix components, such as collagen and hyaluronan. In addition, in vitro and in vivo studies have elucidated the effect of the shape, size and orientation of cells in tissue and cell density on electric field distribution, which are all crucial factors for effective electrotransfection.…”
Section: Electrotransfer Of Tumors M Cemazar Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…This high field is lower than that used for skin (200 V cm À1 ), but much higher than that used in the combination protocol for muscle (80-100 V cm À1 ). 18 The differences in transfection efficiency between different tissues, as well as different tumor histological types, can be explained by the unique characteristics of each tissue, 5,26 namely, the delivery and distribution of macromolecules, including plasmid DNA, is affected by the amount of DNases, necrosis and macrophage infiltration as well as increased interstitial fluid pressure and the amount of extracellular matrix components, such as collagen and hyaluronan. In addition, in vitro and in vivo studies have elucidated the effect of the shape, size and orientation of cells in tissue and cell density on electric field distribution, which are all crucial factors for effective electrotransfection.…”
Section: Electrotransfer Of Tumors M Cemazar Et Almentioning
confidence: 99%
“…[10][11][12][13][14][15][16] A new protocol with high transfection efficacy in muscle and skin has recently been described, consisting of a combination of one high-field (HV, B1000 V cm À1 ) and one (or several) low-field (LV, B100 V cm À1 ) pulse. [17][18][19][20][21][22][23] For simplicity, we called all along the paper 'field' what indeed is the voltage to electrode width ratio, that is, an experimentally controlled parameter. In these studies, the authors suggested two functions of these electric pulses.…”
Section: Introductionmentioning
confidence: 99%
“…This temporary permeabilization of the plasma membrane allows genes or drugs entering into the cell cytosol. This technique is very attractive in various applications such as electrochemotherapy Mir et al 2006), cutaneous and subcutaneous tumour nodule treatments (Mir et al 1998), evaluation of the cytotoxicity of nonpermeant or poorly permeant anticancer drugs (Labanauskiene et al 2007), gene electrotransfer to various animal tissues (Andre and Mir 2004;Andre et al 2008) and latterly with in vivo tests (Gothelf and Gehl 2010;Heller and Heller 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Not only combinations of high voltage pulse (HV) and low voltage pulse (LV) pulses are efficient in skin as well as different kinds of tissues, 29 but also LV pulse combinations are effective in transfecting reporter genes into skin with plate electrodes. 22 …”
Section: In 2001 Maruyama Et Almentioning
confidence: 99%